Edentata 2017
DOI: 10.2305/iucn.ch.2017.edentata-18-1.10.en
|View full text |Cite
|
Sign up to set email alerts
|

First record of the brown-throated sloth (Bradypus variegatus Schinz, 1825) in the Cerrado of Minas Gerais, Brazil

Abstract: Little information is available on the occurrence of sloths in the Cerrado biome in Brazil. Here, we present the first record of Bradypus variegatus in the Cerrado sensu stricto, for the state of Minas Gerais, and possibly for the entire biome. We recorded an adult female at Rio Preto State Park, resting on a mangaba tree (Hancornia speciosa) at an altitude of 1,093 m. The presence of a gallery forest 200 m away suggests that the animal could have come from this and was in the process of dispersal. The sloth p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The species was considered restricted to the Atlantic and Amazon Forests (Paglia et al, 2012), but Moraes-Barros et al (2014) suggest B. variegates can be found in Pantanal and Caatinga. Garcia et al (2017) showed first record of B. variegatus in the Cerrado sensu strict in Minas Gerais. Despite the presence of species in these biomes there are records of small populations isolated in forest fragments (Moraes-Barros et al, 2010;Pedrosa and Castro, 2014;Andrade et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The species was considered restricted to the Atlantic and Amazon Forests (Paglia et al, 2012), but Moraes-Barros et al (2014) suggest B. variegates can be found in Pantanal and Caatinga. Garcia et al (2017) showed first record of B. variegatus in the Cerrado sensu strict in Minas Gerais. Despite the presence of species in these biomes there are records of small populations isolated in forest fragments (Moraes-Barros et al, 2010;Pedrosa and Castro, 2014;Andrade et al, 2020).…”
Section: Introductionmentioning
confidence: 99%